Performance of Clinical Criteria for Screening of Possible Antiretroviral Related Mitochondrial Toxicity in HIV-Infected Children in Accra - Allison Langs-Barlow; Lorna Renner; Karol Katz; Veronika Northrup; Elijah Paintsil (AIDS Research and Treatment)
Mitochondrial damage is implicated in highly active antiretroviral therapy (HAART) toxicity. HIV infection also causes mitochondrial toxicity (MT). Differentiating between the two is critical for HIV management. Our objective was to test the utility of the Mitochondrial Disease Criteria (MDC) and the Enquête Périnatale Française (EPF) to screen for possible HAART related MT in HIV-infected children in Ghana. The EPF and MDC are compilations of clinical symptoms, or criteria, of MT: a (+) score indicates possible MT. We applied these criteria retrospectively to 403 charts of HIV-infected children. Of those studied, 331/403 received HAART. Comparing HAART exposed and HAART naïve children, the difference in EPF score, but not MDC, approached significance (). Young age at HIV diagnosis or at HAART initiation was associated with (+) EPF (). Adherence to HAART trended toward an association with (+) EPF (). Exposure to nevirapine, abacavir, or didanosine increased risk of (+) EPF (OR = 3.55 (CI = 1.99–6.33), 4.76 (2.39–9.43), 4.93 (1.29–18.87)). Neither EPF nor MDC identified a significant difference between HAART exposed or naïve children regarding possible MT. However, as indicators of HAART exposure are associated with (+) EPF, it may be a candidate for prospective study of possible HAART related MT in resource-poor settings.